Linguistic Analysis of Selected Folk Ballads of Mike Ejeagha (2020)
Some earlier studies on Igbo folksongs focused mainly on the thematic and literary study of Igbo folksongs with little attention paid to the linguistic study of Igbo folksongs. To this end, this paper examines some linguistic properties of nine randomly selected works of Mike Ejeagha (ME) that are popular among his audience, with a view to identify and describe the linguistic quality of Igbo folksongs using ME as instance. Data used in the study were collected from ME’s records, transcribed, translated and subjected to descriptive linguistic analysis at the phonological, morphological and syntactic levels. Two phonological processes; vowel assimilation and syllable elision, were identified in the selected works of ME. Reduplication was identified at the morphological level. The syntax of ME arts reveals four syntactic process in his works, such as, topicalisation, negation, question formation and ellipsis to be instrumental in the aesthetics of ME’s art. The study showed that ME employed these linguistic processes repeatedly and consistently to show creativity and achieve stylistic effect in his folk ballads.